2015
DOI: 10.1002/biot.201400620
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ and Mg2+ binding site engineering increases the degradation of polyethylene terephthalate films by polyester hydrolases from Thermobifida fusca

Abstract: Several bacterial polyester hydrolases are able to hydrolyze the synthetic polyester polyethylene terephthalate (PET). For an efficient enzymatic degradation of PET, reaction temperatures close to the glass transition temperature of the polymer need to be applied. The esterases TfH, BTA2, Tfu_0882, TfCut1, and TfCut2 produced by the thermophilic actinomycete Thermobifida fusca exhibit PET-hydrolyzing activity. However, these enzymes are not sufficiently stable in this temperature range for an efficient degrada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
107
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 141 publications
(109 citation statements)
references
References 26 publications
2
107
0
Order By: Relevance
“…The T m and the T5060 values of the disulfide bridge variants were indeed increased by up to 24.9 and 17.3 °C, respectively. Compared to a previously reported increase of T m by 14 °C effected by a substitution of the calcium binding site with a salt bridge, a further gain of more than 10 °C in the T m could thus be obtained . The most stable variant has the D204C‐E253C disulfide bridge.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…The T m and the T5060 values of the disulfide bridge variants were indeed increased by up to 24.9 and 17.3 °C, respectively. Compared to a previously reported increase of T m by 14 °C effected by a substitution of the calcium binding site with a salt bridge, a further gain of more than 10 °C in the T m could thus be obtained . The most stable variant has the D204C‐E253C disulfide bridge.…”
Section: Discussionmentioning
confidence: 69%
“…When the probability density of Ca 2+ within a radius of 3.7 Å to D204C‐E253C was calculated, E26 with a probability density of 42.5 ± 21.0% (SD), D174 with 27.8 ± 20.0%, E202 with 22.4 ± 18.4% and E64 with 21.4 ± 10.4% were observed in close vicinity to the dication. The occupancy map of Ca 2+ in D204C‐E253C revealed that the binding occurred close to the original calcium binding site D174‐D204‐E253 (Fig. ).…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…The resulting monomers are potentially reusable as substrates for polymerization after separation of dyes and contaminants. Protein engineering approaches were used to enable the practical applicability of enzymes in PET degradation and, more specifically, to increase the thermal stability, the activity and the absorption of the enzyme on PET substrates.…”
Section: Enzymatic Degradation and Targeted Modification Of Polyestersmentioning
confidence: 99%